Active screening of magnetic field near power stations generator buses - B.I. Kuznetsov (National Technical University "Kharkiv Polytechnic Institute", 2013)
An experimental study technique for a prototyping system of active screening of power-frequency magnetic field distortions near power station generator buses via controllable magnetic field sources is presented. Results of experimental research on a proto-typing active screening system with different control algorithms are given.